SISTEM PAKAR FORWARD CHAINING , FUZZY-MAX DAN CERTAINTY FACTOR AYAM PEDAGING - Asep Afandi; Dwi Marisa Efendi (Jurnal Informatika, 2021)
Chicken farming is one of the promising business potentials, but in management and care, it is very important to determine the success of chicken farming. Often in the care of negligent employees so that they are exposed to disease outbreaks. With various types of diseases that attack the symptoms are very similar and even the same as other diseases, therefore an expert system can be used to diagnose a disease by looking at the characteristics of the disease suffered, and how the solution is to treat or prevent the disease In the study, it discusses 8 types of broiler diseases, where the expert system method used is the Fuzzy Max method, Forward Chaining, and Certainty Factor. From the results of the Fuzzy Max method, the results showed an accuracy of 80% - 90% for all types of diseases, while the Certainty Factor method showed 96% - 99% for all types of diseases.Keywords— Expert System, Fuzzy Max, Certainty Factor,  Forward Chaining.